2020
DOI: 10.26434/chemrxiv.12994250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organoselenium mild electrophiles in the inhibition of Mpro and SARSCoV-2 replication

Abstract: New Ebselen-like derivatives resulted to be very strong in vitro inhibitors of SARS-CoV-2 main protease. We demonstrated that this activity mainly depends on the electrophilicity of the selenium atom that is considerably higher in the N-substituted 1,2- benzoselenazol-3(2H)-ones respect to the corresponding diselenides allowing it to be rapidly attached by free thiols affording sulfur-selenium intermediates that are further subjected to thiol exchange processes. This data paints a very complex scenario that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A handful of the compounds in this study were further tested in a cell assay. While Se2 was found to have an IC 50 value comparable to Ebselen, Se2 demonstrated a greater activity when compared to Ebselen in the cellular assay, suggesting that derivatization may be useful for obtaining more bioactive compounds in vivo [35] …”
Section: Introductionmentioning
confidence: 98%
“…A handful of the compounds in this study were further tested in a cell assay. While Se2 was found to have an IC 50 value comparable to Ebselen, Se2 demonstrated a greater activity when compared to Ebselen in the cellular assay, suggesting that derivatization may be useful for obtaining more bioactive compounds in vivo [35] …”
Section: Introductionmentioning
confidence: 98%
“…22 Based on these results, other studies have sought to optimize the activity of Ebselen toward SARS-CoV-2, but with limited success. [23][24][25] High-throughput screening studies by Ott et al and others have demonstrated that gold complexes could protect CaCo-2 cells from infections with SARS-CoV-2. 26 Alternatively, [Re(2,2 ′ -bipyridine)(CO) 3 (H 2 O)] + complexes were shown to act as coordinate covalent 3CL pro inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…23 Of pharmacological significance, the plasmatic concentration of (PhSe) 2 after oral administration of relatively high doses to rodents is in the micromolar range. 7,23,37 In this work, after verifying the in vitro (PhSe) 2 effect against SARS-CoV-2 replication, we sought a possible mechanism of action through an in silico approach. For this purpose, we thoroughly analyze in silico the structural and chemical mechanism of SARS-CoV-2 proteases' inhibition by (PhSe) 2 , employing molecular docking, molecular dynamics (MD), and density functional theory (DFT) protocols.…”
Section: Introductionmentioning
confidence: 99%